HUBUNGAN DURASI PEMBERIAN RESTRAIN DENGAN RISIKO PERILAKU MARAH BERULANG PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA Dr. RADJIMAN WEDIODININGRAT LAWANG-MALANG - Icha Suryani; Anndy Prasetya (MEDICA MAJAPAHIT, 2017)
The main problem that often occurs in patients with schizophrenia is violent behavior. Violent behavior is a condition in which a person performs a physically harmful act to himself, others, or the environment. In the management of violent behavior there are 3 prevention strategies, anticipation strategies and restraint strategies. While the binding (restrain) is part of the restraint strategy. This study aims to analyze the relation of duration of restrain administration with risk of recurrent anger behavior in patients with schizophrenia in RSJ. Radjiman Wediodiningrat Lawang, Malang. The design of this study was descriptive correlation with cross sectional study method, by using simple random sampling technique with the number of samples of 32 patients at RSJ Dr. Rdjiman Wediodiningrat Lawang. The study was in April 2017. The result of this research shows that most respondents of violence behavior indicated restrain >4 hours that is 23 respondents (71,9%) and for the risk of repeated violent behaviormost of the respondents are 18 respondents (56,3%). Based on the calculation of Fisher's Exact Test statistics above shows the significance level 0.002 <0.05 then Ho is rejected, which means there is a relation of restrained duration with risk of recurrent anger behavior in patients with schizophrenia in RSJ Dr. Radjiman Wediodiningrat Lawang. Recurrence will not arise if from symptoms that have already made progress. Observation of action is an indicator of the effectiveness, efficiency and quality of care provided to treated patients.